2003
DOI: 10.1094/mpmi.2003.16.5.422
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin from an Incompatible Strain of Acidovorax avenae Mediates H2O2 Generation Accompanying Hypersensitive Cell Death and Expression of PAL, Cht-1, and PBZ1, but Not of LOX in Rice

Abstract: Acidovorax avenae causes a brown stripe disease in monocot plants. We recently reported that a rice-incompatible strain of A. avenae caused hypersensitive cell death in rice and that the flagellin of the incompatible strain was involved in this response. The incompatible strain induced the rapid generation of H2O2 accompanying hypersensitive cell death and the expression of defense genes such as PAL, Cht-1, PBZ1, and LOX, whereas the compatible strain did not. The purified incompatible flagellin also induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…Although, not much is known about its clinical epidemiology and pathogenicity in humans, it has been reported to also degrade nitro-aromatic compounds (Malkan et al, 2009). A potential mechanism for the Acidovoraxadenoma association could relate to the induction of local inflammation by increased flagellar proteins resulting from the higher abundance of Acidovorax (Tanaka et al, 2003;Takakura et al, 2008). Another potential mechanism could be related to changes in the local gut environment that favors increased abundance of specific taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Although, not much is known about its clinical epidemiology and pathogenicity in humans, it has been reported to also degrade nitro-aromatic compounds (Malkan et al, 2009). A potential mechanism for the Acidovoraxadenoma association could relate to the induction of local inflammation by increased flagellar proteins resulting from the higher abundance of Acidovorax (Tanaka et al, 2003;Takakura et al, 2008). Another potential mechanism could be related to changes in the local gut environment that favors increased abundance of specific taxa.…”
Section: Discussionmentioning
confidence: 99%
“…tin, and is expressed following N1141 flagellin infection (20). When cultured rice cells were treated with the S178A and S183A K1 flagellins and S178A/S183A K1 double substituted K1 flagellin, Cht-1 mRNA expression was induced 6 h after treatment.…”
Section: Induction Of Immune Responses In Cultured Rice Cells By Flagmentioning
confidence: 99%
“…We have reported that expression of PAL, which encodes phenylalanine ammonia-lyase and catalyzes the first step in the biosynthesis of lignin monomers and certain classes of phytoalexins, was increased upon the addition of purified N1141 flagellin but not purified K1 flagellin (20). To clarify whether the N1141 flagellin-specific induction of the PAL gene depends on the amino acid residues that are different between the N1141 and K1 flagellins, quantitative real time RT-PCR was performed using the purified and recombinant flagellins.…”
Section: Induction Of Immune Responses By Recombinant Flagellinsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that several immune responses, such as H 2 O 2 generation, hypersensitive cell death accompanied by clear 180-bp nucleosomal DNA laddering, and immune-related genes were induced when cultured rice cells were inoculated with a riceincompatible strain of A. avenae. These responses were completely abolished when a rice-compatible strain of A. avenae was used as the inoculating pathogen (Che et al 1999;Tanaka et al 2001;Iwano et al 2002;Tanaka et al 2003;Fujiwara et al 2004). To identify the specific elicitor related to the induction of these immune responses in cultured rice cells, a strain-specific antibody was raised against the incompatible strain (N1141) and then absorbed by the compatible strain (H8301).…”
mentioning
confidence: 99%